(5x-9)(2x+4)=

Simple and best practice solution for (5x-9)(2x+4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5x-9)(2x+4)= equation:


Simplifying
(5x + -9)(2x + 4) = 0

Reorder the terms:
(-9 + 5x)(2x + 4) = 0

Reorder the terms:
(-9 + 5x)(4 + 2x) = 0

Multiply (-9 + 5x) * (4 + 2x)
(-9(4 + 2x) + 5x * (4 + 2x)) = 0
((4 * -9 + 2x * -9) + 5x * (4 + 2x)) = 0
((-36 + -18x) + 5x * (4 + 2x)) = 0
(-36 + -18x + (4 * 5x + 2x * 5x)) = 0
(-36 + -18x + (20x + 10x2)) = 0

Combine like terms: -18x + 20x = 2x
(-36 + 2x + 10x2) = 0

Solving
-36 + 2x + 10x2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), '2'.
2(-18 + x + 5x2) = 0

Factor a trinomial.
2((-2 + -1x)(9 + -5x)) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(-2 + -1x)' equal to zero and attempt to solve: Simplifying -2 + -1x = 0 Solving -2 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1x = 0 + 2 -1x = 0 + 2 Combine like terms: 0 + 2 = 2 -1x = 2 Divide each side by '-1'. x = -2 Simplifying x = -2

Subproblem 2

Set the factor '(9 + -5x)' equal to zero and attempt to solve: Simplifying 9 + -5x = 0 Solving 9 + -5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -5x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -5x = 0 + -9 -5x = 0 + -9 Combine like terms: 0 + -9 = -9 -5x = -9 Divide each side by '-5'. x = 1.8 Simplifying x = 1.8

Solution

x = {-2, 1.8}

See similar equations:

| -22=-7+3y | | -59+3x=2x+21 | | 5(0)+y=20 | | -7(-5n-2)=119 | | 42=34+q | | Log(x-6)=2 | | -1+6y=14 | | 8(4)(7)-9(3)+4(4)= | | 7x+5=5x-5 | | 10010001001002030+3-10= | | 3x+5=-8(6-5x) | | 11x-47-x=103 | | 4v=8v+32 | | 10m+12n+5m+3n+35= | | 2x-42-7x=84 | | 5x+2(1.5)=10 | | 49-9x+5x=27 | | 10000000000000000000000000000+e= | | 12-7x+4x=27 | | x+7.8=3 | | 2(y+3)=a | | 5(-4)+2y=10 | | 3x+9x-83=73 | | 6.5x+3.5y=9.5 | | 5x+75=10x-5 | | a=2(y+3) | | 6x+4x-97=103 | | 12=5x-9-2x | | -4y-42-3y=5y | | 11x-118-x=38 | | 12x-6x-86=82 | | 6x-8x-22=24 |

Equations solver categories